Promosi E-Ticketing terhadap Kepuasan Konsumen yang Berdampak pada Loyalitas Pelanggan - Maniek, Lindyastuti (Bina Nusantara University, 2013)
Internet causes changes in the behavior of individuals and groups within the business done. With the increasing pressures of globalization, companies struggle to find a way to sustain long-term excellence competitiveness. Competitive advantage is the ability to rapidly innovate and absorb innovations from different sources. The development of e-commerce has increased exponentially. E-commerce has been developed as a new market orientation, creating profit opportunities for growth for many industries. One of the industry's growing use of e-commerce systems is air transport industry. Transport industry is one industry that starts using e-ticketing system, replacing the traditional ticketing system. Replacing the traditional paper ticket electronic ticket has now been proven to be an effective commercial practice for organizations operating in the field of transport. E-ticketing can be described as an alternative method of tickets offered by many flight companies which electronic booking records created contain all the information usually printed on a paper ticket. A new revolution in the aviation industry was created by advances in technology. It changes the way airlines in distributing tickets and requires the flight to the next level. Technology given that the electronic ticket is a technology that utilities actually require universal compatibility across airlines.